Correlations Between Wake Phenomena and Fatigue Loads Within Large Wind Farms: A Large-Eddy Simulation Study - Moens , Maud; Chatelain, Philippe (Frontiers in Energy Research, 2022)
This work proposes a methodology aiming at simulating the whole wind farm behavior, from the wake phenomena to the wind turbine fatigue loads, in a both accurate and efficient way and for a large range of operating conditions. This approach is based on Large Eddy Simulation (LES), coupled to an Actuator Disk (AD) approach. In order to recover pertinent fatigue loads with that wind turbine model, the blade trajectories are replicated through the disk and the AD aerodynamic forces are interpolated onto these “virtual blades” at each time step. The wake centerline is also tracked in the whole wind farm, in order to highlight the correlations between the wake phenomena and the wind turbine fatigue damage. The described methodology is deployed in simulations of the Horns Rev wind farm for several wind directions. The time-averaged power production is first compared to measurements and other LES results, with a very good agreement for large wind sectors. We then investigate the fatigue loads for several machines inside the wind farm and wind directions. We clearly show the link between the upstream wake movement and the resulting high and low frequency oscillations of the root bending moments and of the yaw and tilt moments, and therefore on the resulting fatigue equivalent loads. This study demonstrates the capacity of the numerical tool to accurately capture the wind farm flow and the rotor behaviors, as well as the correlations between the wake phenomena and the resulting fatigue loads.